A compact and wideband array antenna with efficient hybrid feed network. Issue 11 (12th August 2020) - Karami, Farzad; Rezaei, Pejman; Amn‐e‐Elahi, Ali; Meiguni, Javad Soleiman
Abstract: This study presents a high‐efficient, compact, and broadband microstrip patch antennas (MPAs) based on substrate‐integrated waveguide (SIW) for X‐band applications. The proposed array consists of three stacked layers from top to bottom, including one layer as the antenna layer and two SIW layers as a feeding network. The performance was focused on improving the impedance bandwidth and radiation efficiency by mitigating the loss from the feed network while also maintaining the compact design. To this end, the SIW feeding network was designed to feed the MPA to save the physical aperture size which resulted in a more compact and efficient radiating structure. The overall size of the proposed array is compact and extra surface area around the radiation aperture has not been occupied. The measured −10 dB impedance bandwidth span is from 8.9 to 10.9 GHz (20.2%). The maximum measured gain at 10.6 GHz is 10.6 dBi. The results show that the simulated radiation efficiency and the measured aperture efficiency are more than 75% and 50%, respectively. The fabricated array exhibits great advantages such as wide operating bandwidth, lightweight, low‐cost, high aperture efficiency, high radiation efficiency, and compactness which make it a good candidate for X‐band applications.